Cardiovascular risk in Hashimoto thyroiditis patients according to their thyroid state: a cross-sectional study (Ciencia y Salud, 2023)
Aims: To investigate the association between cardiovascular risk factors and cardiovascular risk score with the thyroid status of patients with Hashimoto’s Thyroiditis.Methods: Thirty-eight consenting adults with Hashimoto’s Thyroiditis participated in this cross-sectional study. The cardiovascular risk factors considered included age, sex, blood pressure, body mass index, fast blood glucose, lipid profile, cardiovascular comorbidities, C reactive protein, and erythrocyte sedimentation rate. The Framingham CV risk score was performed. The sample was classified into euthyroid (n = 15), clinical hypothyroidism (n = 9), and subclinical hypothyroidism (n = 13), and included the presence of antithyroid antibodies. Fisher’s exact test was used to determine the association between the variables studied.Results: 100% of the sample were women; a mean age between 39-59 years old. The category with low risk was the largest (n = 30), equivalent to 78.9%; moderate risk, no patient was obtained; high risk (n = 8) constituted 21.1%. Statistical significance between age and CV risk score in patients with clinical hypothyroidism was found (p < 1), 95% CI. The glucose level in the subclinical hypothyroidism and clinical hypothyroidism had statistical significance. The presence of anti-Thyroglobulin (antiTg) was shown to be closely related to the level of CV risk in patients with subclinical hypothyroidism.Conclusion: Age, glycemia, anti-Tg, history of DM, dyslipidemia, or cerebrovascular accidents have been linked to raising the risk of developing CVD in up to 10 years depending on their thyroid profile. No evidence of a direct relationship between CV risk score and thyroid state was found in the participants of this study.